2018
DOI: 10.1016/j.cophys.2017.12.013
|View full text |Cite
|
Sign up to set email alerts
|

De novo mutations and rare variants occurring in NMDA receptors

Abstract: A significant number of variants/mutations in the -methyl--aspartate glutamatergic receptor (NMDAR) gene family () have been identified along with stunning advances in the technologies of next generation of whole-exome sequencing. Mutations in human genes are distributed throughout the entire gene, from amino terminal domain to C-terminal domain, in patients with various neuropsychiatric disorders, including autism spectrum disorders, epilepsy, intellectual disability, attention deficit hyperactivity disorder,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
140
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 116 publications
(142 citation statements)
references
References 84 publications
2
140
0
Order By: Relevance
“…Impaired NMDAR function observed during human NMDAR gene mutations [104], and anti-NMDAR-encephalitis [105] results in a wide range of neuropsychiatric disorders including autism spectrum disorders [106, 107], intellectual disability [108], psychosis [109], epilepsy and associated comorbidities [110, 111]. While broadly aberrant NMDAR signaling in neurons is thought to underlie a wide range of these neurological disorders, an interneuron-centric developmental NMDAR aberration is emerging central to schizophrenia-related syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired NMDAR function observed during human NMDAR gene mutations [104], and anti-NMDAR-encephalitis [105] results in a wide range of neuropsychiatric disorders including autism spectrum disorders [106, 107], intellectual disability [108], psychosis [109], epilepsy and associated comorbidities [110, 111]. While broadly aberrant NMDAR signaling in neurons is thought to underlie a wide range of these neurological disorders, an interneuron-centric developmental NMDAR aberration is emerging central to schizophrenia-related syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid expansion of whole-exome sequencing over the last decade has shown that many regions of the gene encoding GluN2A (GRIN2A) are intolerant of variation in healthy controls (Ogden et al 2017) and, instead, a large number of rare and de novo variants (>100) have been identified in patients with a range of neurodevelopmental disorders, most commonly epilepsy aphasia syndromes or other epileptic disorders, but also intellectual disability, autism, attention deficit hyperactivity disorder and schizophrenia (XiangWei et al 2018). At the most severe end of the phenotypic spectrum are epileptic encephalopathies, where epileptic activity is considered to contribute to severe cognitive and behavioural impairment (Scheffer et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic variants in GRIN genes are associated with developmental and early onset epileptic encephalopathies (DEE) with accompanying comorbidities, such as intellectual disability, autism, aphasia, and schizophrenia (Endele et al, 2010;Hamdan et al, 2011;de Ligt et al, 2012;Lesca et al, 2013;Petrovski and Kwan, 2013;Yuan et al, 2015;Hu et al, 2016;XiangWei et al, 2018). A variety of GRIN2A variants are associated with epilepsies, presumably due to haploinsufficiency or alteration of receptor properties.…”
Section: Introductionmentioning
confidence: 99%